Materials Challenges 2014
DOI: 10.1039/9781849733465-00135
|View full text |Cite
|
Sign up to set email alerts
|

Thin Film Cadmium Telluride Solar Cells

Abstract: This chapter discusses a number of deposition techniques used to produce polycrystalline CdTe solar cells, including progress of photovoltaic (PV) performances in recent years. Focus is on the CdTe absorber and the effects from impurities, which are dependent on the process conditions used, but also due to self-compensating nature of the material itself influencing the acceptor levels in the layer. Impurities can introduce deep donor/acceptor levels that act as traps for both majority and minority carriers. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 81 publications
(193 reference statements)
0
3
0
Order By: Relevance
“…At the same time, the ICP analysis revealed that the amount of Hg decreased from 1% at 200 °C to below the detection limit at 350 °C. Overall, these results were quite remarkable, considering that to sinter a film of colloidal CdTe NCs, one would typically require annealing temperatures above 350 °C. , Indeed, as a control, we observed that a non-exchanged CdTe NC sample annealed at 200 °C did not undergo any appreciable sintering (Table and Figure S5).…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…At the same time, the ICP analysis revealed that the amount of Hg decreased from 1% at 200 °C to below the detection limit at 350 °C. Overall, these results were quite remarkable, considering that to sinter a film of colloidal CdTe NCs, one would typically require annealing temperatures above 350 °C. , Indeed, as a control, we observed that a non-exchanged CdTe NC sample annealed at 200 °C did not undergo any appreciable sintering (Table and Figure S5).…”
Section: Resultsmentioning
confidence: 66%
“…Spherical CdTe NCs, with a mean diameter of 4.5 ± 1 nm, were synthesized following the procedure reported by Zhang et al (see Figure a). The elemental analysis, conducted via ICP-OES, revealed that the composition of the NCs was nearly stoichiometric (i.e., CdTe), and the XRD characterization indicated the presence of a mixture of both CdTe wurtzite (WZ) and zinc blende (ZB) structures (ICSD numbers 620518 and 43712, respectively) (Figure c, blue pattern and Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation